Nurse Prescribing of Opioid Agonist Treatment in Ireland: Evidence, Governance, and the Politics of Drug Policy Decision-Making - Kelly, Peter; James, Philip; Comiskey, Catherine; Mc Brien, Barry (My University, 2026)
Globally, opioid agonist treatment (OAT) is recognised as a cornerstone of evidence-based responses to opioid dependence. Many countries have expanded access by enabling nurses to prescribe methadone and buprenorphine, with consistent evidence of safety, effectiveness, and improved equity of access. Despite this precedent, Ireland has not introduced nurse prescribing of OAT. Drawing on policy reviews, communications, national strategy documents, legislation, parliamentary debates, international literature and media reports, this commentary positions this issue as an important initiative which has been excluded from Irish drug-policy. This commentary highlights a clinical and regulatory paradox: Irish nurses may prescribe controlled opioids for pain and palliative care for a person who is dependent on opioids, but are legally prohibited from prescribing the same medications for OAT. Independent reviews and government policy have recommended exploring nurse prescribing to address persistent workforce shortages. This commentary identifies how governance structures have marginalised nursing perspectives and mobilised evidence selectively, contributing to inaction. The authors propose that this case illustrates how existing approaches, varying accountability, and political framing shape policy decisions. With a new national drugs strategy in development, Ireland faces a choice: continue with non-inclusive, traditional governance or adopt inclusive, evidence-informed reform that aligns with international best practice.
PUBLISHED
https://doi.org/10.1016/j.drugpo.2026.105153
Keywords: Opioid agonist therapy; Nurse prescribing; Governance; Drug policy; Ireland; Harm reduction; Inclusive Society; Smart & Sustainable Planet; Addiction and substance abuse; Health Disparities; Leadership in nursing; Nursing; Public health; Chronic Health Condition; Mental Health/Psychosocial disability; Health; Policy; Social exclusion; Social services, interventions and supports